2018
DOI: 10.3233/jhd-170274
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Mutant Huntingtin Protein Levels Decline with Age in Homozygous Huntington’s Disease Knock-In Mouse Models

Abstract: Background Huntington’s disease (HD) is a progressive neurodegenerative disorder associated with aging, caused by an expanded polyglutamine (polyQ) repeat within the Huntingtin (HTT) protein. In HD, degeneration of the striatum and atrophy of the cortex are observed while cerebellum is less affected. Objective To test the hypothesis that HTT protein levels decline with age, which together with HTT mutation could influence disease progression. Methods Using whole brain cell lysates, a unique method of SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
3
7
2
Order By: Relevance
“…1, Supplementary Figure 4). While previously reported that transgene expression was within range of the endogenous murine gene in R6/2 mice [10], there was a moderate increase in the levels of endogenous Htt transcript in R6/2 mice in this study by 11 weeks of age in the striatum compared to age-matched NT controls, perhaps indicating an upregulation to compensate for transgene genotoxic stress or for the declining wild-type endogenous HTT protein levels observed in HD knock-in mice during aging [34]. Intriguingly, this increase also extended to expression of the R6/2 transgene in striatum, potentially reflecting compensatory upregulation of Htt given that the transgene is expressed from the human Htt promoter [10].…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…1, Supplementary Figure 4). While previously reported that transgene expression was within range of the endogenous murine gene in R6/2 mice [10], there was a moderate increase in the levels of endogenous Htt transcript in R6/2 mice in this study by 11 weeks of age in the striatum compared to age-matched NT controls, perhaps indicating an upregulation to compensate for transgene genotoxic stress or for the declining wild-type endogenous HTT protein levels observed in HD knock-in mice during aging [34]. Intriguingly, this increase also extended to expression of the R6/2 transgene in striatum, potentially reflecting compensatory upregulation of Htt given that the transgene is expressed from the human Htt promoter [10].…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed, in the assays here, decreasing monomeric mHTTex1p from fractionation of striatal tissue or breaking in RIPA appeared qualitatively to track most closely with the progression of phenotypes in the R6/2 mice. We have previously published a decrease in full-length HTT with age in striatum and cortex of two HD homozygous knock-in models and in wild-type controls, which may reflect a loss of full-length HTT protein function over time [34]. Due to the dynamic shift between mHTTex1p conformations throughout the course of the disease we propose using multiple, optimized biochemical analyses, potentially in combination with high context histological approaches as described for knock-in zQ175 mice [39] to determine the impact of potential therapeutics on the protein flux of both mHTTex1p and full-length HTT protein.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our data suggest that earlier age of onset in Q140 as compared to HdhQ150 mice, for the sensorimotor and pathological phenotypes that we have assessed, may be caused by the increased levels of exon 1 HTT. However, our data do not rule out the contribution of other factors, for example, the differences between the mouse and human polyproline regions of exon 1 present in HdhQ150 and Q140, although functional consequences of these sequence differences at the protein level have not been identified, and levels of full length mutant HTT have been reported to decrease more slowly with age in HdhQ150 than in Q140 mice (Franich et al, 2018). Nevertheless, our data suggest that targeting the production and/ or levels of the Httexon1 transcript, presents a rational approach to complement existing therapeutic strategies.…”
Section: Discussioncontrasting
confidence: 77%